PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT. BPR MITRA RUKUN MANDIRI - Insani, Vivie; Saragih, Romat (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2017)
Every company must have a goal to achieve. Manpower (human resources) is a main key in achieving the goals of the company, therefore the company requires good quality of human resources to obtain the expected performance. One way that can be done to improve performance is to implement the right leadership style This study aims to analyze the influence of the leadership style on employee performance in PT BPR Mitra Rukun Mandiri Bandung. Sampling technique was saturation sampling type under non-probability sampling, where all population was used as research sample with the total number of 35 respondents. The technique of analysis used simple regression analysis. The result of research shows that Leadership Style is in quite good category and Employee Performance is in low category. Based on hypothesis test, the result shows leadership style significantly influences employee performance at PT. BPR Mitra Rukun Mandiri Bandung. Keywords: Leadership Style, Employee Performance, Human Resources Management